Strategy of employing plug-and-play vectors and LC–MS screening to facilitate the discovery of natural products using Aspergillus oryzae - Hanliang Shi; Beibei Lin; Mengmeng Zheng; Fengyu Gan; Zhi Lin; Xiujuan Xin; Jian Zhao; Xudong Qu; Faliang An (Bioresources and Bioprocessing)
Abstract Aspergillus oryzae is a widely used host for heterologous expression of fungal natural products. However, the vectors previously developed are not convenient for use and screening positive transformants by PCR and fermentation is time- and effort-consuming. Hence, three plug-and-play vectors were developed here for multi-gene expression and liquid chromatography mass spectrometry detection was introduced to screen positive transformants. Using rug BGC for verification, we demonstrated that the vectors we developed perform well and liquid chromatography mass spectrometry detection is feasible to screen positive transformants. For deleterious gene expression, PxyrA rather than PamyB was employed. Utilizing the toolkit described here to express natural products, dozen days can be saved. Graphical Abstract